Hardboard from Unbarked Eucalyptus Hybrid - Chauhan, B. R. S.; Bist, J. P. S. (Indian Forester, 1987)
Large scale plantations of Eucalyptus hybrid bave been raised in the country in degraded forests, road side land, canal banks, community lands etc., and it is expected that substantial quantity of wood would be available in future for various wood processing industries. The wood waste like bark, tops, thinnings, twigs etc., which accounts considerable volume of a tree would also be available which largely find use as fuel. Therefore, the suitability of unbarked Eucalyptus hybrid including tops, thinnings, twigs etc., was studied for hardboard manufacture. It was established that unbarked Eucalyptus hybrid is a suitable raw material for hardboard manufacture. The standard hardboards could be prepared with additive after heat tempering and tempered boards after oil tempering only using the semi-chemlcal process.